Second Five-Year Plan (1956-61) Revised Draft Proposals - Planning Commission (Planning Commission, 1955)
One of the principal objectives of the First Five-Year Plan, 1951-56, was to make India largely self-sufficient in food and the main emphasis in the Plan was therefore on Agriculture and Irrigation. Many major Irrigation and Power projects were being implemented in the Madras State from 1946 onwards as part of the Post-War. Reconstruction Programme and as considerable progress had been made in the execution of these projects, they had, of necessity, to be included in the First Five-Year Plan for the State and the provision for such projects amounts to over Rs. 51 crores out of the total Plan provision of Rs. 86’43 crores for the State excluding Community Development and other Centrally sponsored schemes.
Madras State Revised Draft Proposals